CT diagnosis and destiny of acute aortic intramural hematoma - Giacomo Sica; Gaetano Rea; Roberta Lieto; Mariano Scaglione; Ahmad Abu-Omar; Giorgio Bocchini; Federica Romano; Salvatore Masala; Stefania Tamburrini; Salvatore Guarino; Candida Massimo; Tullio Valente (Frontiers in Radiology)
Acute aortic intramural hematoma (IMH) is a relatively uncommon but potentially life-threatening aortic disease that can occur primarily in hypertensive and atherosclerotic patients. The course of IMH varies widely, with the condition either regressing, remaining stable, or progressing until it leads to outward rupture or intimal layer disruption, eventually resulting in overt aortic dissection. Therefore, poor prognostic computed tomography (CT) features must be promptly recognized and reported by the radiologist. In emergency departments, readily accessible non-invasive CT angiography is crucial for achieving a rapid and accurate diagnosis essential for appropriate management. For Type A and B aortic dissection, surgery is typically recommended in Western countries for patients with Stanford Type A IMH and those experiencing irrepressible pain. For Stanford Type B IMH patients without complications or incessant pain, medical treatment is suggested but with imaging follow-up. In complicated Stanford Type B situations, thoracic endovascular aortic repair (TEVAR) is currently indicated. This review aims to present pathophysiology, CT diagnosis, and IMH fate and provide the reader CT image-based review of the CT diagnostic criteria, complications, and associated critical prognostic findings of this rather rare aortic disease.